A circRNA-miRNA-mRNA network plays a role in the protective effect of diosgenin on alveolar bone loss in ovariectomized rats - Zhiguo Zhang; Lifeng Yue; Yuhan Wang; Yanhua Jiang; Lihua Xiang; Yin Cheng; Dahong Ju; Yanjing Chen (BMC, 2020)
Abstract Background The present study aimed to assess the perturbation in circular RNA (circRNA)/mRNA expression profiles and a circRNA-miRNA-mRNA coexpression network involved in the potential protective effect of diosgenin (DIO) on alveolar bone loss in rats subjected to ovariectomy (OVX). Methods The Wistar rats (female) manipulated with sham operation were classified as the SHAM group and the grouping of OVX rats administered with DIO, estradiol valerate or vehicle for 12 weeks was DIO group, EV group and OVX group respectively. Following treatments, the plasmatic levels of osteocalcin and tumor necrosis factor-alpha and the microstructure of alveolar bone were assayed. Based on microarray analyses, we identified differentially expressed (DE) circRNAs and mRNAs in alveolar bone of rats in both OVX and DIO group. The DE circRNAs and DE mRNAs involved in the bone metabolism pathway validated by RT-qPCR were considered key circRNAs/mRNAs. On the basis of these key circRNAs/mRNAs, we predicted the overlapping relative miRNAs of key circRNAs/mRNAs, and a circRNA-miRNA-mRNA network was built. Results DIO showed an anti-osteopenic effect on the rat alveolar bone loss induced by OVX. In total, we found 10 DE circRNAs (6 downregulated and 4 upregulated) and 614 DE mRNAs (314 downregulated and 300 upregulated) in samples of the DIO group compared with those of the OVX group. However, only one circRNA (rno_circRNA_016717) and seven mRNAs (Sfrp1, Csf1, Il1rl1, Nfatc4, Tnfrsf1a, Pik3c2g, and Wnt9b) were validated by qRT-PCR and therefore considered key circRNA/mRNAs. According to these key circRNA/mRNAs and overlapping predicted miRNAs, a coexpression network was constructed. After network analysis, one circRNA-miRNA-mRNA axis (circRNA_016717/miR-501-5p/Sfrp1) was identified. Conclusion The mechanism of DIO inhibiting alveolar bone loss after OVX is possibly relevant to the simultaneous inhibition of osteogenesis and osteoclastogenesis by mediating the expression of important molecules in the Wnt, PI3K, RANK/RANKL or osteoclastogenic cytokine pathways. The circRNA_016717/miR-501-5p/Sfrp1 axis may play important roles in these processes.